2015
DOI: 10.4238/2015.april.13.12
|View full text |Cite
|
Sign up to set email alerts
|

Expression of β-defensins in intestines of chickens injected with vitamin D3 and lipopolysaccharide

Abstract: ABSTRACT. The objective of this study was to evaluate the effect of vitamin D 3 (VD 3 ) on the regulation of chicken intestinal b-defensin genes under normal and lipopolysaccharides (LPS) conditions. Four treatment groups were used, including a negative control group, VD 3 -injection group, LPS-injection group, and both VD 3 -injection and LPS-injection group. At 4, 24, and 48 h post-injection, intestines were collected and RNA was isolated to measure the chicken b-defensin genes with putative vitamin D respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 30 publications
3
16
0
Order By: Relevance
“…These observations support the results of previous reports, showing that the AvBD genes were expressed in the small intestine and cecum of embryos and chicks (Akbari et al, 2008;Crhanova et al, 2011;Hong et al, 2012;Lu et al, 2015;Zang et al, 2016;Su et al, 2017;Terada et al, 2018). AvBD2 in the mucosal leukocytes (Terada et al, 2018) and AvBD9 in enteroendocrine cells from the luminal and crypt epithelia have also been reported (Cuperus et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…These observations support the results of previous reports, showing that the AvBD genes were expressed in the small intestine and cecum of embryos and chicks (Akbari et al, 2008;Crhanova et al, 2011;Hong et al, 2012;Lu et al, 2015;Zang et al, 2016;Su et al, 2017;Terada et al, 2018). AvBD2 in the mucosal leukocytes (Terada et al, 2018) and AvBD9 in enteroendocrine cells from the luminal and crypt epithelia have also been reported (Cuperus et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…Prior studies in our lab demonstrated that injection of Vit-D 3 is able to modulate AvBD gene expression in intestinal tissues [ 23 ]. To confirm the previous results, CEIEPCs were used as a model to evaluate the action of 1,25D 3 on the expression of AvBDs with or without LPS.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the presence of potential VDREs in the promoters of chicken AvBDs [ 23 ], we hypothesized 1,25D 3 may increase the relative mRNA abundance of some AvBD genes through VDREs. In this experiment, CHX pretreatment completely inhibited 1,25D 3 -mediated up-regulation of three AvBD genes in PBMCs, however, CHX further increased the expression of CYP24A1 , the primary VDR/1,25D 3 target gene [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The innate immune response is the first line of defense against infection. The epithelial cells of the intestinal mucosa facilitate efficient host defense by producing the HDP genes [34], which plays a significant role in the chicken innate immune system, providing the first line of defense against potential pathogens [16,22,35,36]. We found that the Daweishan mini chickens showed the highest mRNA levels of HDP genes mRNA in small intestine tissue while Avian broilers exhibited the lowest mRNA levels of HDP genes.…”
Section: Hdp Genes In the Small Intestinementioning
confidence: 78%